2005
DOI: 10.1021/jp052222v
|View full text |Cite
|
Sign up to set email alerts
|

Deuterium Isotope Effects on the Interaction between Hyperbranched Polyethylene Imine and an Anionic Surfactant

Abstract: Solvent isotope effects on the interaction between the hyperbranched cationic polyelectrolyte, polyethylene imine (PEI), and the anionic surfactant sodium dodecyl sulfate (SDS) were investigated using potentiometric titration and eletrophoretic mobility measurements. In the basic pH range, a significantly higher fraction of the amine groups was found to be protonated when the PEI was dissolved in D2O compared to H2O at the same pH/pD. The difference in polymer charge in the two solvents decreases gradually wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 25 publications
4
32
1
Order By: Relevance
“…The aggregates change to a more complex three-dimensional structure with increasing surfactant concentration. [32] Similarly, in the current study three dimensional structures were observed at a SDS concentration starting from 4 Â 10 À3 M in the presence of PEI (400 ppm) at pH 9.…”
Section: Pei/sds Interactions 25supporting
confidence: 75%
See 2 more Smart Citations
“…The aggregates change to a more complex three-dimensional structure with increasing surfactant concentration. [32] Similarly, in the current study three dimensional structures were observed at a SDS concentration starting from 4 Â 10 À3 M in the presence of PEI (400 ppm) at pH 9.…”
Section: Pei/sds Interactions 25supporting
confidence: 75%
“…As the surfactant association proceeds three-dimensional aggregates, involving several polyelectrolyte chains and SDS, can be formed. [32] In the current study SDS=PEI complexation at high pH is driven by the cooperative interaction of the surfactant via uncharged nitrogen atoms of the amine groups. [33,4] Additionally, hydrophobic interactions is the mechanism that dominates SDS=PEI interaction at high pH.…”
Section: Pei/sds Interactions 25mentioning
confidence: 91%
See 1 more Smart Citation
“…The interactions between copolymers with nonionic and oppositely charged surfactants have been studied extensively [8][9][10][11][12][13][14][15]. Since the interaction is believed to be weak or nonexistent, interactions between polyelectrolytes and surfactants with the same charge are less extensively studied.…”
Section: Introductionmentioning
confidence: 99%
“…BASF and Hyperpolymers commercialized the hyperbranched polyethyleneimine (PEI) via the self‐condensing proton‐transfer polymerization of ethylene imine. Such PEIs as well as their quaternized derivatives have been well studied in various applications 19–23…”
Section: Introductionmentioning
confidence: 99%